Kadar Indeks Eritrosit Pada Pekerja Peleburan Logam Berdasarkan Studi Literatur - Widhi Ulya Syamputri (Jaringan Laboratorium Medis, 2021)
The metal smelting industry tends to have high air Pb levels exceeding the threshold determined by the CDC is 100 g/m3. The smelting dust particles are Pb and SO2 circulating in the air along with combustion fumes is very possible to be inhaled by metal smelters who do not wear proper personal protective equipment. High levels of Pb The air inhaled by metal smelters can affect the health level of workers, one of which is the disruption of the erythropoiesis process which can cause abnormal erythrocyte index levels. This study aims to determine the description of erythrocyte index levels in metal smelters based on literature studies. This research is an observational qualitative research through a literature review approach, with data collection methods that use secondary data from several related scientific journals. Secondary data analysis is descriptive and presented in tabular form. Based on the results of research from three related scientific journals, the average level of the erythrocyte index in metal smelting workers is normochromic normocytic with an average length of work of more than 3.89 years, workers who smoke as much as 78% and those who do not smoke as much as 22%, workers who using PPE as much as 56% and 44% who do not use PPE.